CO2 capture from biogas by biomass-based adsorbents: A review. (15th November 2022) - Aghel, Babak; Behaein, Sara; Alobiad, Falah
Graphical abstract: Highlights: Recent advances in biogas upgrading by biomass-based adsorbents are reviewed. An overview of the production process through activation, and characteristics of adsorbent. Recyclability and selectivity of biomass-based adsorbents for CO2 capture have been studied. Selection of appropriate chemical additives can be considerably enhanced the CO2 adsorption capacities. Abstract: Biogas is one of the most important renewable energy sources containing methane, carbon dioxide, and small amounts of other gases and water. Raw biogas cannot be used because CO2 and other inert gases reduce the energy content of biogas and calorific value. Biogas upgrading significantly improves the quality of biogas by removing CO2 . One of the leading technologies of biogas enrichment is using an adsorption method on activated carbons due to their high selectivity for removing CO2 . Activated carbon is a good choice due to its high adsorption capacity at atmospheric pressure, lower cost, hydrophobic properties, high surface area, and the ability to modify pore structure and surface performance. On the other hand, the massive production of agricultural waste and biomass negatively affects the environment, so recycling biowaste into valuable materials is essential economically and environmentally. To recycle and convert biowaste, activated carbon is simply made through carbonization and can be used as suitable adsorbents for separating gaseous mixtures, including CH4 /CO2 . In this review, bio-based adsorbents were investigated in porosity, morphology, composition, selectivity, and CO2 capture to upgrade biogas.